Estudio clínico e histopatológico del carcinoma epidermoide en cavidad oral - Romero Rivas, Roberto (2002)
This paper searches apidermoid carcinoma in oral cavity with the highest prevalence in oral palate 70% cases with clinical values T4, G2, G3 and clinical stage E4 with bad prognosis. Treatment included oral suegery, radical ganglionar excision and radiotherapy. The next highest prevalence was around the tongue, in its posterolingual side with 20%, irs clinical values were T3, G2 and clinical stage E3 with mild prognosis. Treatment included radiotherapy, oral surgery was highly traumatic. The labial ocurrence reached 10% with clinical values TI, G0 and clinical stages El with good prognosis. Last case was a verrugosa leucoplasia with clinical value TIS, G0, E0 with very good prognosis with complete excision as unique treatment. They were made histopathological analysis in all cases.